جنحة عدم تسديد نفقة - نادية صالحي نويوة صبرينة (جامعة المسيلة, 2022)
خلاصة القول أن النفقة موضوع مهم جاز البحث فيه والنظر للإشكالات التي تحيط به، لأن قانون الأسرة الجزائري اعتبر النفقة هي الإعالات المقررة قضاء للفرد لصالح أسرته، سواء زوجته أو فروعه أو الأصول، وبهذا أجاز للقاضي أن يحكم على كل من هو ملزم بها لدفعها لمستحقيها، كما أنه يجوز الصفح فيها، ووقع العقوبة على من يخالف هذا الالتزام. الكلمات المفتاحية: النفقة، الأصول، الفروع، الجزاء، العقاب. Abstract: In sum, alimony is an important topic that it is permissible to discuss and consider the problems surrounding it, because the Algerian family law considered alimony to be the maintenance determined for the individual for the benefit of his family, whether his wife, descendants or assets, and thus allowed the judge to rule on everyone who is obligated to pay it to those who deserve it, It is also permissible to forgive them, and the penalty is imposed on anyone who violates this obligation key words: Alimony, assets, branches, penalty, punishment.
Keywords: النفقة، الأصول، الفروع، الجزاء، العقاب